The Role of E-Learning as a Learning Media in Schools - Didik Himmawan; Faqih Faizal Rahman; Suwarno (Ilmina: Journal of Education and Counseling, 2025)
This paper aims to determine the influence of E-learning as a learning medium in schools. It is expected that educators and those related to education can maximize this opportunity well so that they can motivate students to learn. This study investigates the influence of E-learning as a learning medium in schools. By collaborating between library research and conducting observations and interviews. The results show that E-learning can improve classroom learning by utilizing technology to support more effective, dynamic, and inclusive learning.